THE INFLUENCE OF USING ORTHOSES PROSTHESES FOR FOR PEOPLE WITH DISABILITIES TO THE QUALITY OF LIFE ON SPECIAL HEALTH COVERAGE IN BAPEL JAMKESOS REGION OF YOGYAKARTA - Setiyawan, Sholeh; Adistyawan, Guritno; Setyowati, Lilis (Rumah Sakit Akademik Universitas Gadjah Mada, 2023)
Background : Quality of life is an assessment of individual welfare that can be felt in daily life includes many aspects such as emotions, social, and physical in the lives of individuals. The quality of life of people with disabilities needs to be assessed and evaluated to see the extent of changes that occur after receiving comprehensive medical rehabilitation services. Subjects and method: The method used is descriptive quantitative analysis. Data collection is done by questionnaire method (questionnaire). The data obtained will be processed using SPSS 17.0. The population of this study were patients with disabilities in the Province of D.I. Yogyakarta, especially patients receiving assistance from the Ortose Prostese at Bapel Jamkesos D.I. Yogyakarta as many as 30 people. Results : A complete description of the 8 aspects of quality of life is 1) Limitations of physical activity due to existing health problems, the results are 65.34% unlimited, 2) Limitations of social activities due to physical and emotional problems, the results are 66.68% unlimited, 3) Limitations of daily activities due to physical problems, the results are 81.65% unlimited, 4) whole body pain, the result is 58.3% do not feel the pain means, 5) mental health in general, the results are 39.62% have a life spirit 6) Limitations of daily activities because of emotional problems, the results are 53.3% unlimited, 7) vitality of life, the results are 70.85% feeling good and 8) health views in general, the results are 51.65% feeling very good. Conclusion: People with disabilities are mostly being distracted on mental health and morale aspect, however, for daily activities mostly do not any experience problems or physical disorders, so the Ortose Prostese that used by patient can provide benefits and improve their quality of life.